2020
DOI: 10.1093/molbev/msaa230
|View full text |Cite
|
Sign up to set email alerts
|

Modularity in Protein Evolution: Modular Organization and De Novo Domain Evolution in Mollusk Metallothioneins

Abstract: Metallothioneins (MTs) are proteins devoted to the control of metal homeostasis and detoxification, and therefore, MTs have been crucial for the adaptation of the living beings to variable situations of metal bioavailability. The evolution of MTs is, however, not yet fully understood, and to provide new insights into it we have investigated the MTs in the diverse classes of Molluscs. We have shown that most molluscan MTs are bi-modular proteins that combine six domains –α, β1, β2, β3, γ and δ– in a lineage spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 67 publications
3
45
0
Order By: Relevance
“…The high negative charge of the unique metal-sulfur clusters, such as the Zn 4 Cys 11 -α-clusters and Zn 3 Cys 9 -β-clusters in MT-1 and MT-2, is balanced by seven lysine residues, resulting in the equally unique dumbbell shape of the MT proteins which sets them apart from many other biomolecules found in nature [ 38 , 39 ]. Other primary structures of MTs comprising diverse Cys content and coordination, hence varying in metal load and affinities, have been documented [ 40 , 41 , 42 ].…”
Section: The Enigmatic Role Of Vertebrate Mtsmentioning
confidence: 99%
See 4 more Smart Citations
“…The high negative charge of the unique metal-sulfur clusters, such as the Zn 4 Cys 11 -α-clusters and Zn 3 Cys 9 -β-clusters in MT-1 and MT-2, is balanced by seven lysine residues, resulting in the equally unique dumbbell shape of the MT proteins which sets them apart from many other biomolecules found in nature [ 38 , 39 ]. Other primary structures of MTs comprising diverse Cys content and coordination, hence varying in metal load and affinities, have been documented [ 40 , 41 , 42 ].…”
Section: The Enigmatic Role Of Vertebrate Mtsmentioning
confidence: 99%
“…Still, the widespread prevalence of MTs across organisms and their unique biochemical properties suggest that MTs serve, or at least have served, as we shall elaborate below, some important biological role(s). Recent studies have reported a divergence in the function(s) of MTs based on the type of cysteine motifs in invertebrates and vertebrates [ 40 , 47 ]. The new γ domain identified in Patellogastropoda, for instance, favors cadmium over zinc and is more resilient against demetallation [ 40 ].…”
Section: The Enigmatic Role Of Vertebrate Mtsmentioning
confidence: 99%
See 3 more Smart Citations